Pengalaman Narrative Transportation dalam Menonton Film Bergenre Drama - Arafi Aditya Putra; Dede Lilis Chaerowati (Bandung Conference Series: Public Relations, 2024)
Abstract. This research discusses the Narrative Transportation experience of viewers in watching drama genre films, in the context of the film community. The main focus of this research is to understand how viewers are actively involved and immersed in the narrative world presented by films, as well as how this experience influences their understanding, emotions and behavior. This research aims to explore in more depth the experience of watching films and their impact on everyday life, as well as the contribution of the film community in shaping viewers' perceptions and behavior towards this medium. This research uses qualitative methods with a phenomenological approach and interpretive paradigm. The object of this research is the phenomenon of narrative transportation, including situations where individuals are completely transported into the narrative. Meanwhile, the research subjects were student members of the community who watched films. The results showed that members of the Free Film Productions community experienced strong Narrative Transportation when watching drama genre films, which resulted in deep emotional and cognitive involvement. This experience makes them feel more understanding and connected to the characters and plot in the film, influencing their perception of reality and shaping their behavior in everyday life. These findings emphasize the important role of the film community in deepening the viewing experience and shaping audience perceptions and behavior towards the film medium. Abstrak. Penelitian ini membahas pengalaman Narrative Transportation penonton dalam menonton film bergenre drama, dalam konteks komunitas film. Fokus utama penelitian ini adalah untuk memahami bagaimana penonton terlibat secara aktif dan tenggelam dalam dunia naratif yang disajikan oleh film, serta bagaimana pengalaman tersebut memengaruhi pemahaman, emosi, dan perilaku mereka. Penelitian ini bertujuan untuk mengeksplorasi lebih dalam mendalam tentang pengalaman menonton film dan dampaknya dalam kehidupan sehari-hari, serta kontribusi komunitas film dalam membentuk persepsi dan perilaku penonton terhadap medium tersebut. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi dan paradigma interpretif. Objek penelitian ini adalah fenomena narrative transportation mencakup situasi di mana individu terbawa sepenuhnya ke dalam narasi. Sedangkan subjek penelitian adalah mahasiswa anggota komunitas yang menonton film. Hasil penelitian menunjukkan bahwa anggota komunitas Free Film Productions mengalami Narrative Transportation yang kuat saat menonton film bergenre drama, yang menghasilkan keterlibatan emosional dan kognitif yang mendalam. Pengalaman ini membuat mereka merasa lebih memahami dan terhubung dengan karakter serta plot dalam film, mempengaruhi persepsi mereka terhadap realitas dan membentuk perilaku mereka dalam kehidupan sehari-hari. Temuan ini menegaskan pentingnya peran komunitas film dalam memperdalam pengalaman menonton dan membentuk persepsi serta perilaku penonton terhadap medium film.